Automated accounting system for Pangasinan State University-Urdaneta Campus - Bernisca, Rhenel R. (2015)
This study aimed to develop an Automated Accounting System for Pangasinan State University-Urdaneta City Campus. Specifically, it determined the capabilities and constraints of the existing accounting system in terms of performance, information, economics, control, efficiency, and service, developed the Automated Accounting System, evaluated its usability. This study was a descriptive and developmental type of research. It assessed the status of the current accounting system by administering PIECES survey questionnaire to the Accountant, Accounting administrative aids, and Cashier staffs. It followed the Rational Process Model to design and develop the Automated Accounting System. Further, it evaluated its usability by administering SUMI questionnaire to IT experts, Accountant, Accounting administrative aids, Cashier staffs. and to the University's Chief Finance Officer. The study found out that: The Current system is a constraint in terms of performance, information economy, control and efficiency and capable in service; RUP model paved way to the development of Automated Accounting System; The Automated Accounting System was evaluated usable. Based on the aforementioned findings, the following conclusions were derived: The current system needs to be improved in terms of performance, information, economy, control and efficiency while upholding better service; The Automated Accounting System is worthy for implementation because it was evaluated usable.
Keywords: Accounting -- Software; Information and communication technologies -- Educational use; Pangasinan State University (Urdaneta)